Bilan 2024 du statut des ressources halieutiques débarquées par la pêche française hexagonale en 2023 - Vermard, Youen; Ulrich, Clara (2025)
This report, updated annually, details the composition of French landings (by weight, but also by number of exploited populations) caught in the North-East Atlantic and the Mediterranean by species and geographical unit ("fish stock"), according to their status with regard to the Maximum Sustainable Yield (MSY) objective. This represents an assessment of the interaction between these resources and their exploitation. In this 2025 report, the reference year is 2023, with assessments carried out in 2024. Fish landings in mainland France totalled 323,000 tonnes in 2023, down 7% on the previous year. 169 exploited populations of 73 species are scientifically monitored and assessed ("stocks"), 134 of which are classified in relation to the Fmsy, Bref and Blim reference points. 58% of the volumes of fish landed in 2023 come from non-overfished populations, known as "sustainably exploited", i.e. with a fishing mortality less than or equal to the Fmsy value defined by the Common Fisheries Policy. Since 2017, this proportion of sustainably fished populations has increased very little. This year, the report also presents new information on recent recruitment trends, for stocks for which this information is available. 31% of the volume of fish landed comes from populations whose recruitment is declining and only 20% comes from populations whose recruitment is increasing. Data are insufficient for the remaining 49%. The report also provides maps showing the geographical location of landings according to their exploitation status. Ce rapport, mis à jour annuellement, détaille la composition des débarquements français hexagonaux (en poids, mais aussi en nombre de populations exploitées) capturés dans le Nord-Est Atlantique et la Méditerranée par espèce et unité géographique (« stock halieutique »), en fonction de leur statut au regard de l'objectif du rendement maximal durable (RMD). Cela représente ainsi un bilan de l’interaction entre ces ressources et leur exploitation. Dans ce rapport 2025, l’année de référence est ...